1994
DOI: 10.3382/ps.0730408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ochratoxin A and Diacetoxyscirpenol Singly and in Combination on Broiler Chickens

Abstract: The effects of feeding 2 mg ochratoxin A (OA) and 6 mg 4,15-diacetoxyscirpenol (DAS)/kg of diet singly and in combination were characterized in male broiler chicks from 1 to 19 d of age. Body weights were depressed by OA, DAS, and the OA-DAS combination. There was a significant antagonistic interaction between OA and DAS for uric acid and cholesterol. The efficiency of feed utilization was reduced by DAS alone and by the OA-DAS combination. When compared with controls, additive toxicity was exhibited for reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
3
15
2
Order By: Relevance
“…Total protein concentration was mostly in agreement with the values described as physiological (Sirvydis et al 2006;Stevanovi} et al 1990). Similar results were reported by some authors (Kubena et al, 1985b;Kubena et al 1989;Kubena et al, 1994) although several authors (Ayed et al, 1991;Singh et al, 1990) reported somewhat higher values as normal proteinaemia in broilers. In the blood serum of experimental groups, mild differences influenced by OTA treatment were seen, but with no statistical significance.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Total protein concentration was mostly in agreement with the values described as physiological (Sirvydis et al 2006;Stevanovi} et al 1990). Similar results were reported by some authors (Kubena et al, 1985b;Kubena et al 1989;Kubena et al, 1994) although several authors (Ayed et al, 1991;Singh et al, 1990) reported somewhat higher values as normal proteinaemia in broilers. In the blood serum of experimental groups, mild differences influenced by OTA treatment were seen, but with no statistical significance.…”
Section: Resultssupporting
confidence: 92%
“…In the blood serum of experimental groups, mild differences influenced by OTA treatment were seen, but with no statistical significance. These findings did not confirm the results obtained by Kubena et al, (1985b); Kubena et al, (1989); Kubena et al, (1994) who suggested that the total blood serum protein concentration significantly decreased after treatment with OTA. On the other hand, the obtained results confirmed the findings of others authors (Huff and Ruff, 1981;Singh et al, 1990) who suggested that the total blood serum protein concentration was not significantly decreased after treatment with lower levels of dietary OTA.…”
Section: Resultscontrasting
confidence: 81%
See 3 more Smart Citations